Effect of corrugated skins on the aerodynamic performance of the cambered airfoils. Issue 3 (8th May 2018) - Kharati-koopaee, Masoud; Fallahzadeh-abarghooee, Mahmood
Abstract : Purpose: This paper aims to study the effect of corrugated skins on the aerodynamic performance of the cambered NACA 0012 airfoils at different corrugations parameters, maximum cambers, Reynolds numbers and maximum camber locations. Design/methodology/approach: In this work, numerical approach is concerned, and results are obtained based on the finite volume approach. To characterize the effect of corrugated skins, the NACA 0012-corrugated airfoil section is chosen as the base airfoil, and different cambered corrugated airfoil sections are obtained by inclusion the camber to the base airfoil. In this research, the corrugation shape is a sinusoidal wave and corrugated skins are in the aft 30 per cent of airfoil chord. To investigate the effect of corrugations on the cambered sections, the drag coefficient and averaged lift curve slope for the corrugated airfoils are compared to those of the corresponding smooth sections. Findings: Results indicate that the effect of increase in the maximum camber and also Reynolds number on the relative zero-incidence drag coefficient is of little importance at low corrugation amplitudes, whereas at high corrugation, amplitude results in different behaviors. It is found that as the maximum camber increases, the deterioration in the relative curve slope introduced by corrugated skins is reduced, and reduction in this deterioration is significant for high corrugation amplitudes airfoils. It is shown that an increase in the maximum camber location has nearly no effect on the relative zero-incidence drag coefficient and also relative lift curve slope. Originality/value: The outcome of the present research provides the clues for better understanding of the effect of different corrugations parameters on the aerodynamic performance of the unmanned air vehicles to have as high aerodynamic performance as possible in different mission profiles of such vehicles.